Advancements In Stem Cell Therapy For Pulmonary Fibrosis: A Comprehensive Review With Vinski Protocol - Deby Susanti Pada Vinski Vinski; Jaime Rodriguez Quintosa; Andi Ibnu Hajar; Natasha Cinta Vinski; Andi Kurniawan Nugroho (Riviera Publishing, 2025)
Pulmonary fibrosis (PF) is a progressive interstitial lung disease characterized by scarring of lung tissue and limited treatment options, resulting in high morbidity and poor prognosis. Mesenchymal stem cell (MSC) therapy has emerged as a promising regenerative intervention due to its potential for immunomodulation, epithelial repair, and anti-fibrotic effects. This review synthesizes current clinical and observational studies involving human participants, highlighting the safety and preliminary therapeutic benefits of MSCs in managing PF and related pulmonary conditions. Several clinical trials involving patients with idiopathic pulmonary fibrosis and COVID-19-associated lung injury demonstrated favorable safety profiles and trends toward improved pulmonary outcomes. Additionally, observational findings from the application of the Vinski Protocol at Celltech Stem Cell Centre provide further support for the regenerative capabilities of MSCs. While current human studies are encouraging, further large-scale and long-term clinical trials are essential to validate the efficacy of MSC therapy and establish standardized treatment protocols for PF.